2011
DOI: 10.1016/j.biopsycho.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system reactivity to positive and negative mood induction: The role of acute psychological responses and frontal electrocortical activity

Abstract: The differential effects of positive versus negative emotions on autonomic nervous system activity are insufficiently understood. This study examined the role of acute mood responses and central nervous system activity on heart rate variability (HRV) using 5-min event recall tasks (happiness and anger recall) and a 5-min Stroop Color Word Test (SCWT) in 20 healthy individuals (mean age 25±4 years, 55% female). HRV was measured in high frequency (HF) and low frequency (LF) domains, and frontal brain activity us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 72 publications
7
125
2
1
Order By: Relevance
“…1 Order of procedures for the second session physiological equipment that made writing difficult. This protocol has often been used by researchers employing emotional recall tasks because particular emotions are distinctly associated with parasympathetic and sympathetic physiological reactivity (Kop et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…1 Order of procedures for the second session physiological equipment that made writing difficult. This protocol has often been used by researchers employing emotional recall tasks because particular emotions are distinctly associated with parasympathetic and sympathetic physiological reactivity (Kop et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the use of specific patterns of autonomic activity as an indicator for specific emotions is disputed. There are certainly characteristics of sympathetic/parasympathetic activity and respiration that are correlated with certain emotional states such as anxiety or happiness (Kop et al 2011). We propose that negative mood states such as stress, anxiety, and depression cause sympathetic activation that is due to widespread depolarization throughout the brain and body, and that slow, deep breathing and meditation lead to parasympathetic activation due to widespread inhibition and hyperpolarization.…”
Section: Introductionmentioning
confidence: 97%
“…In our study Alpha 2 activity increased meaningfully with response to sad emotion more specifically in Fz (mid frontal zone) there are few studies conducted with respect to Fz area in the past (15). In Kops's study, electrophysiological responses like HRV (Heart Rate Variability) related to emotions were assessed (27). It has been demonstrated that in emotional disorders, alpha variability occurs in frontal regions.…”
Section: Discussionmentioning
confidence: 65%